Complete mitochondrial genome of the Southern two-lined salamanders (Eurycea cirrigera). Issue 2 (12th December 2017) - Wang, XingRan; Li, Junkui; Zhang, LiNa; Li, HongQing; Ma, Kai; Han, Ying
Abstract: The complete mitochondrial genome of the southern two-lined salamanders ( Eurycea cirrigera) was determined in this study. The complete mitogenome sequence of E. cirrigera is 16, 759bp in length and contains 37 genes (13 protein coding genes (PGCs), two ribosomal RNA, 22 transfer RNA genes and one control region). This is the first time of the mitochondrial genome sequencing for E. cirrigera.